Finite groups with complementable maximal primary cyclic subgroups - Mel'nik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study finite nonprimary groups with complementable maximal primary cyclic subgroups and give a description of all supersolvable groups of this sort.